Choosing a CRRT machine and modality. Issue 6 (26th October 2021) - Macedo, Etienne; Cerdá, Jorge
Abstract: Expanded use and steady improvements in continuous renal replacement techniques (CRRT) have enhanced the safety of the application of kidney replacement therapy (KRT) to hemodynamically unstable intensive care unit (ICU) patients. The longer duration of therapy and the personalized prescription provided by continuous therapies are associated with greater hemodynamic stability and a modestly higher likelihood of kidney recovery than standard intermittent hemodialysis (IHD). Studies designed to evaluate the effect on mortality over intermittent therapies lack evidence of benefit. A lack of standardization and considerable variation in how CRRT is performed leads to wide variation in how the technique is prescribed, delivered, and optimized. Technology has progressed in critical care nephrology, and more progress is coming. New CRRT machines are equipped with a friendly user interface that allows easy performance and monitoring, permitting outcome measurements and improved patient quality control. This review discusses the key concepts necessary to guide nephrologists to prescribe and deliver KRT to critically ill ICU patients.